Effects of Maternal Dexamethasone Treatment Early in Pregnancy on Glucocorticoid Receptors in the Ovine Placenta. (May 2015) - Shang, H.; Meng, W.; Sloboda, D. M.; Li, S.; Ehrlich, L.; Plagemann, A.; Dudenhausen, J. W.; Henrich, W.; Newnham, J. P.; Challis, J. R. G.; Braun, T.
The effects of endogenous cortisol on binucleate cells (BNCs), which promote fetal growth, may be mediated by glucocorticoid receptors (GRs), and exposure to dexamethasone (DEX) in early pregnancy stages of placental development might modify this response. In this article, we have investigated the expression of GR as a determinant of these responses. Pregnant ewes carrying singleton fetuses (n = 119) were randomized to control (2 mL saline/ewe) or DEX-treated groups (intramuscular injections of 0.14 mg/kg ewe weight per 12 hours) at 40 to 41 days of gestation (dG). Placental tissue was collected at 50, 100, 125, and 140 dG. Total glucocorticoid receptor protein (GRt) was increased significantly by DEX at 50 and 125 dG in females only, but decreased in males at 125 dG as compared to controls. Glucocorticoid receptor α (GRα) protein was not changed after DEX treatment. Three BNC phenotypes were detected regarding GRα expression (++, +−, −−), DEX increased the proportion of (++) and decreased (−−) BNC at 140 dG. Effects were sex- and cell type dependent, modifying the responsiveness of the placenta to endogenous cortisol. We speculate that 3 maturational stages of BNCs exist and that the overall activity of BNCs is determined by the distribution of these 3 cell types, which may become altered through early pregnancy exposure to elevated glucocorticoids.